Analysing Farmers’ Perceptions of Genetically Improved G3 Rohu (Labeo rohita) Fish Culture in Mymensingh District, Bangladesh - Sharmin Akter; Nura Azim; Mohammad Jiaul Hoque; Mithun, Md. Nur Alom Sarkar; Solaiman Saad; Md. Abid Hasan (Indian Journal of Extension Education, 2025)
Growing G3 rohu (Labeo rohita) fish can improve nutritional stability, raise farmer incomes, boost productivity, and promote sustainable aquaculture. The study evaluated fish farmers’ perceptions of G3 Rohu culture and identified the socio-economic and contextual factors influencing these perceptions. A pre-tested structured interview was conducted with 105 fish farmers, representing 50% of the total, in the Phulpur sub-district of Mymensingh district, Bangladesh, between February and May 2023. A 5-point Likert scale with 12 statements (six positive and six negative) was used to measure perceptions. Data analysis included both descriptive and inferential statistics. Results revealed that 74.3% of farmers had a favourable perception, while 25.7% reported a highly favourable perception; no respondents indicated unfavourable views. Regression analysis revealed that, among the twelve independent variables, area under fish culture, area under Rohu fish culture, organisational participation, and extension media contact significantly and positively influenced farmers’ perception levels of G3 Rohu fish culture. Conversely, household size and social mobility showed negative effects. Furthermore, it is recommended that increasing organisational participation and extension services, while addressing socioeconomic hurdles, can support the widespread adoption of G3 Rohu breeds for long-term aquaculture flourishing in Bangladesh.